2022
DOI: 10.3390/vaccines10101702
|View full text |Cite
|
Sign up to set email alerts
|

Global Excess Mortality during COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: Background: Currently, reported COVID-19 deaths are inadequate to assess the impact of the pandemic on global excess mortality. All-cause excess mortality is a WHO-recommended index for assessing the death burden of COVID-19. However, the global excess mortality assessed by this index remains unclear. We aimed to assess the global excess mortality during the COVID-19 pandemic. Methods: We searched PubMed, EMBASE, and Web of Science for studies published in English between 1 January 2020, and 21 May 2022. Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…However, this is not supported by the results of Figure 7 which shows an increase in transactions during that time frame. This is further supported by marked increases in COVID-19 cases in the US [32]. Another explanation is that the March 2020 spike corresponded to several U.S. state and local lockdowns going into effect.…”
Section: Covid-19 Abstractmentioning
confidence: 73%
See 1 more Smart Citation
“…However, this is not supported by the results of Figure 7 which shows an increase in transactions during that time frame. This is further supported by marked increases in COVID-19 cases in the US [32]. Another explanation is that the March 2020 spike corresponded to several U.S. state and local lockdowns going into effect.…”
Section: Covid-19 Abstractmentioning
confidence: 73%
“…Social media-based infoveillance is an important modality to limiting disease spread and ultimately saving lives. While data collection infrastructure has been deployed in a variety of forms globally, distrust of both public and private solutions (e.g., contact tracing apps) and substantial privacy concerns have prevented them from becoming widely adopted in countries like the U.S. (where a disproportionate number of COVID-19 deaths occurred [32]). It is critical that a privacy-utility balance is found to benefit future data collection methods.…”
Section: Discussionmentioning
confidence: 99%
“…The literature confirms these findings since several studies found that males, older nurses, and those with a chronic condition had a higher intention to accept primary COVID-19 vaccination and booster doses [ 21 , 48 , 49 , 50 , 72 ]. It is well known that COVID-19-related severe outcomes such as hospitalization, mechanical ventilation, and mortality are higher among males, the elderly, and individuals with comorbidity [ 73 , 74 , 75 ]. Thus, it is probable that perceived risk of COVID-19 and fear about the disease are higher among nurses that belong to high-risk groups, leading to a higher acceptance rate of booster doses.…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation between excess mortality and GDP per capita has been observed before. It has been seen for Spanish flu (26) and for COVID-19 pandemic (27,28). Even at the single-country level, the excess mortality associated with COVID-19 is inversely correlated with the average family income that existed in the area of residence (25).…”
Section: Low Gdp Low Vaccination Rates and High Pandemic-associated M...mentioning
confidence: 99%